Предмет: Алгебра,
автор: yangurazova2018
Упростите выражение х(х – 1)(х – 1) – (х – 2)(х2 +2х +4)
Ответы
Автор ответа:
2
Условие не пишу
=х^3-х^2+х-х^2+х^3-2х^2+2х^2--4х+4х-8=-2х^2+х-8
=х^3-х^2+х-х^2+х^3-2х^2+2х^2--4х+4х-8=-2х^2+х-8
Автор ответа:
7
x(x - 1)(x - 1) - (x - 2)(x² + 2x + 4) = x(x² - 2x + 1) - (x³ - 2³) =
= x³ - 2x² + x - x³ + 8 = - 2x² + x + 8
= x³ - 2x² + x - x³ + 8 = - 2x² + x + 8
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: artembajkov19
Предмет: Физика,
автор: RipVip
Предмет: Алгебра,
автор: dmuhivan